Prediction of Global, Diffused and Direct Solar Radiation for Oriented and Inclined Surface Based on Meteorological Data for efficient energy use in the south of Tunisia - mahmoud ben amara; Elhem Rdhaounia; moncef balghouthi (Journal of Engineering Research - Egypt)
The determination of solar radiation data at a given geographic location is very important for the development of solar applications and for the evaluation of their performances. The current paper provides the determinations for horizontal, inclined and oriented surface the global, diffuses and direct solar radiation by making the comparison between “MATLAB” simulation model and the climatology measured data for ten years provided by a high precision meteorological station installed in Tataouine (32°93′latitude, 10°45′ longitude) in the south of Tunisia where the available solar resources are very important. The global and direct solar radiation variability was assessed on hourly, monthly and seasonally scales. The statistical test methods were used in order to indicate the performance of the model. It shows a good potential for the use in estimating values of solar radiation components on different surface`s kinds in the nearby locations where measurements of the sunshine data are not available. Such accurate knowledge is very useful for the site selection of solar power plants for both photovoltaic and concentrated thermal systems.